2003
DOI: 10.1007/s00216-003-2021-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential analysis of phosphorylated proteins in resting and thrombin-stimulated human platelets

Abstract: Blood platelets are important components of haemostasis. After their activation they cause healing of wounds by forming plugs and initiate repair processes. One important event in regulating this activation is the phosphorylation/dephosphorylation of multiple proteins on various tyrosine, serine and threonine residues. To understand the exact molecular mechanisms in platelet activation it is essential to identify proteins involved in the signalling pathways and to localise and characterise their phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 91 publications
1
57
0
Order By: Relevance
“…In one study, proteins from resting and collagen receptor-stimulated platelets were incubated with cAMP/cGMP-coupled beads, and the pull-down eluates were analyzed by LC-MS/MS. 115 Owing to the enrichment provided by specific probes, activity-based protein profiling 116-121 B, These studies are mainly (40%) based on 2-dimensional gel electrophoresis (2-DE)/ difference gel electrophoresis (DIGE), 46,52,53,80,82,83,85,87,88,90,91,[93][94][95][96]98,102,106,110,112,113 whereas gelfree methods (23%) are still under-represented. 21,42,89,97,[114][115][116][117][118]121 Combination refers to studies using 2-DE/DIGE in combination with other approaches.…”
Section: Platelet Subproteomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, proteins from resting and collagen receptor-stimulated platelets were incubated with cAMP/cGMP-coupled beads, and the pull-down eluates were analyzed by LC-MS/MS. 115 Owing to the enrichment provided by specific probes, activity-based protein profiling 116-121 B, These studies are mainly (40%) based on 2-dimensional gel electrophoresis (2-DE)/ difference gel electrophoresis (DIGE), 46,52,53,80,82,83,85,87,88,90,91,[93][94][95][96]98,102,106,110,112,113 whereas gelfree methods (23%) are still under-represented. 21,42,89,97,[114][115][116][117][118]121 Combination refers to studies using 2-DE/DIGE in combination with other approaches.…”
Section: Platelet Subproteomesmentioning
confidence: 99%
“…In contrast, state-of-the-art procedures use quantitative phosphoproteomics to monitor changes in phosphorylation levels of hundreds to thousands of peptides from relatively low sample amounts (≈0.1-1 mg of protein per condition), thus providing valuable insights into important biochemical processes. To date, mostly gel-based approaches in conjunction with phosphotyrosine immunoprecipitation have been used to study platelet signaling processes (eg, mediated by activation of thrombin receptors, 93,106,107,137 collagen receptors, 82,112 C-type lectin-like receptor 2, 138 and integrin α IIb β 3 outside-in signaling). 139 Because of the limitation in sensitivity, these approaches often did not provide MS-based identification of phosphorylation sites but identified new phosphoproteins and signaling pathways, hence expanding the knowledge about platelet regulation.…”
Section: Ptm and Signaling Proteomics In Plateletsmentioning
confidence: 99%
“…Early studies identified phosphorylated proteins in thrombin-activated platelets (43,44,53), and enrichment for phosphotyrosine-containing proteins by immunoprecipitation detected 67 proteins that were differentially phosphorylated between resting and thrombinactivated platelets. Through the application of MALDI-TOF, the identity of 10 of these, including FAK and SYK, was confirmed (40).…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…Likewise, the identification of 27 proteins that translate to the platelet cytoskeleton, upon thrombin stimulation, was demonstrated by 2-DE and MS [151]. A differential analysis of phosphorylated proteins in resting and thrombin stimulated platelets identified 55 proteins [148]. In a similar strategy Garcia et al [152], identified 62 proteins differentially expressed by platelets activated in vitro.…”
Section: Plateletsmentioning
confidence: 97%
“…These studies have been extended and novel platelet signaling proteins and phophorylation events have been identified [145][146][147][148][149]. Using LC-MS/MS, lectin affinity chromatography and free flow electrophoresis, has permitted the identification of novel transmembrane proteins in human platelets [150].…”
Section: Plateletsmentioning
confidence: 99%